The role of sensory systems in the management of difficult-coordinated movements of athletes - Ровний Анатолій Степанович (Anatoliy Rovnyy); Ровна Ольга Олександрівна (Olga Rovna); Галімський Володимир Олександрович (Volodymir Galimskyi) (Slobozhanskyi Herald of Science and Sport, 2014)
Purpose: based on the theory of functional systems to determine the mechanism of sensory motor control human system approach. Materials and methods: analysis and generalization of scientific works of 60 native and foreign authors. Results: It was found that motor control involves all sensory systems, but the dominant role is played by one touch system or by its separate function. Others play a complementary role. Conclusions: A complex intra- and inter-system communication of sensory systems as the main coordinator in motor control.